Budaya Islam Sub-Urban: Studi Sosio-kultural Tradisi Upacara di Desa Candipari Kecamatan Porong Sidoarjo - Syam, Nur; Nurhalizah, Mevy Eka (The Sociology of Islam, 2021)
This study tries to answer how the local traditions of the people of Candipari Village with a socio-cultural approach. The method used is descriptive qualitative with interviews and documentation as data collection techniques. Based on the theory of social construction, it is known that the socio-cultural reality is constructed by the view of Hinduism. Ceremonial traditions are influenced by local culture, the traditions of our ancestors, and global cultures such as religion. In the process of externalization, a process of fusion between the two cultures occurs, namely the tradition of ancestors and Islam, which causes objectification in the form of Islamization of social reality and the loss of the caste system, and in the process of internalization is to preserve these local traditions to the present. Then the researcher examines the theory of social action. The local tradition is included in the type of Wert Rational or rational action based on values, namely the value of belief in God about salvation, and the type of Traditional Action which is social action based on past traditions. Then, in relation to the concept of collaborative Islam, the tradition of using the Pari Temple as a cultural space for the gathering of village communities, this is because not all village communities are Muslim. The tradition is also still preserved as a legacy of ancestors even though it has become a local Islamic tradition. This is a form of social construction of agents or elders towards ordinary people through continuous communication.